2020
DOI: 10.1038/s41533-020-0166-2
|View full text |Cite
|
Sign up to set email alerts
|

Planned primary health care asthma contacts during 12-year follow-up after Finnish National Asthma Programme: focus on spirometry

Abstract: Primary health care (PHC) providers are at the front line of asthma management. To evaluate how planned asthma follow-up occurred in PHC and whether lung function tests were used, 203 patients were followed for 12 years as part of a real-life asthma cohort Seinäjoki Adult Asthma Study (SAAS). A total of 152 patients had visits in PHC attending on average to four planned contacts during 12-year follow-up corresponding to one visit every third year. National guideline recommends annual visits. Patients with ≥4 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 56 publications
3
33
0
Order By: Relevance
“… 14 Among asthmatics in Finland, the follow-ups occurred generally every third year. 31 However, follow-up visits were recently shown to be more common among those with GINA step 4/5 treatment and those with exacerbations compared to the lower treatment steps and those without exacerbations. 32 It is vital that all individuals with potentially severe asthma have regular contact with a healthcare provider because asthma symptoms and the risk of exacerbation vary with time.…”
Section: Discussionmentioning
confidence: 99%
“… 14 Among asthmatics in Finland, the follow-ups occurred generally every third year. 31 However, follow-up visits were recently shown to be more common among those with GINA step 4/5 treatment and those with exacerbations compared to the lower treatment steps and those without exacerbations. 32 It is vital that all individuals with potentially severe asthma have regular contact with a healthcare provider because asthma symptoms and the risk of exacerbation vary with time.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] After asthma diagnosis was confirmed and medication initiated the patients were managed by their personal physicians mostly in PHC according to the Finnish National Asthma Programme [ 22 ] unless asthma severity or other respiratory diseases required monitoring in specialized care. As described previously[ 2 , 4 , 15 , 21 ], after 12 years (mean 12.2, range 10.8–13.9) a total of 203 patients completed a follow-up visit where the participants gave written informed consent to the study protocol approved by the Ethics committee of Tampere University Hospital, Tampere, Finland (R12122). In addition to the data gathered at the diagnostic and follow-up visits, all data on asthma-related health care contacts during 12-year period was collected from PHC, occupational health care, private clinics and secondary care [ 2 , 4 , 15 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…As described previously[ 2 , 4 , 15 , 21 ], after 12 years (mean 12.2, range 10.8–13.9) a total of 203 patients completed a follow-up visit where the participants gave written informed consent to the study protocol approved by the Ethics committee of Tampere University Hospital, Tampere, Finland (R12122). In addition to the data gathered at the diagnostic and follow-up visits, all data on asthma-related health care contacts during 12-year period was collected from PHC, occupational health care, private clinics and secondary care [ 2 , 4 , 15 , 21 ]. The SAAS-study protocol has been published previously [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The REcognise Asthma and LInk to Symptoms and Experience survey of 8000 adults with asthma in 11 European countries, including Sweden, showed that acute exacerbations were common and that 12% of the patients with asthma had been hospitalized because of asthma during the previous year. 14 Also, a recent study from Finland showed that the frequency of asthma follow-up contacts is insufficient, with only 1 of 3 patients with asthma attending a planned visit each year, 15 as recommended by guidelines. 11 Although poor asthma control still leads to hospitalizations, few contemporary population-based studies have investigated the management, treatment patterns, and risk of rehospitalization and mortality in patients with asthma postdischarge.…”
Section: Introductionmentioning
confidence: 99%